Bullying experience in urban adolescents: Prevalence and correlations with health-related quality of life and psychological issues. - Anh Toan Ngo; Long Hoang Nguyen; Anh Kim Dang; Men Thi Hoang; Trang Huyen Thi Nguyen; Giang Thu Vu; Hoa Thi Do; Bach Xuan Tran; Carl A Latkin; Roger C M Ho; Cyrus S H Ho (PLoS ONE)
This study examined the 3-month rate of bullying experience, associated factors, and measure the relationships between bullying experience with health-related quality of life and different mental disorders among secondary school students. We performed a cross-sectional study in four secondary schools in Hanoi, Vietnam. Bullying experience was evaluated by using questions about eighteen specific-bullying behaviors. EuroQol-5 dimensions-5 levels (EQ-5D-5L) and Depression, Anxiety, and Stress Scale- 21 items (DASS-21) were used to measure health-related quality of life (HRQOL) and mental health of participants, respectively. Among 712 secondary school students, the 3-month prevalence of physical, social aggression, verbal, and sexual bullying experience were 8.4%; 31.2%; 11.9%, and 2.7%, respectively. Being bullied were negatively associated with levels of classmates and family support, as well as levels of school security. Being overweight or obese was related to a higher likelihood of suffering social aggression compared to normal BMI. Being bullied was significantly associated with the decrement of HRQOL, and the increased risk of depression, anxiety, and stress among adolescents. Findings of this study suggested that holistic approaches involving family, peers, and schools, along with enhancing school security, are potential approaches to reduce the impact of bullying on adolescents' life and well-being.